The New Kingdom Royal City - Peter Lacovara (USA Kegan Paul International, 1997)
This study reveals a highly diversified and unique pattern of habitation in the Nile Valley. The main focus of this work is the New Kingdom, which offers the largest number of sites from any one period. Previously most studies of Egyptian urbanism have focused exclusively on the site of Tell el-Amarna, which has become the paradigm for ancient Egyptian settlements. Critical to our understanding of Egyptian urbanism is the question of just how representative of pharaonic town planning Amarna truly is. To resolve this problem, this study contrasts Amarna with what available data exists from other sites. One important source for such a comparison is the Second Intermediate Period site of Deir el-Ballas. This 'incipient Amarna' may well have served as the prototype for the revised urbanism of the New Kingdom. This study also reviews the data from other New Kingdom settlements on a 'micro-spatial' level, dealing with both the arms of individual structures as well as the overall community layout. Comparisons between the overall plans of the various settlements and the various elements which comprise them reveal a 'mental template' of urban structure that existed in ancient Egypt.
Ch. 1. Town Planning in Ancient Egypt: Historical Overview -- Ch. 2. Domestic Architecture: Palaces -- Ch. 3. Domestic Architecture: Administrative and Support Buildings -- Ch. 4. Domestic Architecture: Workmen's Villages -- Ch. 5. Domestic Architecture: Private Houses -- Ch. 6. The Royal City -- Ch. 7. Ancient Egyptian Urban Design -- Ch. 8. Deir el-Ballas and the Development of the New Kingdom Royal City.
Keywords: Cities and towns, Ancient -- Egypt; City planning -- Egypt -- History; Architecture -- Egypt; General; Ancient Egypt; Archaeology